Frictional Heat Generation and Geothermal (Global Journal of Science Frontier Research, 2022)
The article starts from the natural phenomenon of sparks in the stone tip, analyzes the essence of frictional heat generation, and deduces the theory of pressure heat generation. Geocentric, geothermal, and solar source issues are explained.
Keywords: structural energy; relative motion; high temperature liquid state; ion heating; quantum heart; sphere collapse; geomagnetism; geothermal